Employment challenges among persons with disabilities in Malaysia - Abd Manaf, Abdul Razak; Othman, Siti Zubaidah; Mohd Isa, Mohd Faizal; Wan Mohd Noor, Wan Shakizah; Azizan, Norizan (HRMAS, 2019)
Job participation among the disabled in Malaysia remains a complex issue. Despite the initiative and efforts being undertaken by various parties, this widely debated topic yet to be solved amicably. With the emergence of information and communication technology, the field of employment for persons with disabilities should have changed and created a new horizon for the disabled where they can work from home. But, the number of disabled employed by public or private organizations remained small. Therefore, the main objective of this study is to explore employment issues among Persons with Disabilities (PWDs) in Malaysia. To uncover these issues, input from 225 employed PWDs themselves were solicited through an on-site semi-structured interview. The results showed that among the crucial issues surrounding employability of PWDs in the workforce were due to negative perceptions from employers and peers, accessibility issues, lack of training, lack of support from family and personal attributes of PWDs themselves. Based on the findings of the study, several suggestions and recommendations were put forward to increase participation of PWDs in the workforce.